Perkutane Nadelaponeurotomie bei Dupuytren-Kontraktur - Oppermann, Johannes; Unglaub, Frank (Der Orthopäde, 2017)
Dupuytren disease is a benign fibroproliferative disease of the palmar aponeurosis, which can cause considerable functional deficiencies for the person concerned. Partial aponeurectomy is the gold standard in primary surgery. Because it is minimally invasive and has short recovery and low complication rates, the importance of needle aponeurotomy under specific indications has been increasing in the last years. Needle aponeurotomy is a cost-effective treatment with low complication rates. The revision rate compared to partial aponeurectomy is higher. Under consideration of specified indications, needle aponeurotomy is an alternative treatment option.
Gesehen am 01.06.2018